The effect of water hardness on viability and hatching percentages of Asian catfish, Claria macrocephalus (Gunther) eggs. - Palma, Rex Vener Palmares (1997.)
An investigation was conducted to established the optimum water hardness during incubation of Asian catfish, Clarias macrocephalus (Gunther) eggs to improve hatching., Eggs were incubated at four levels of water hardness: <100ppm, 100 ppm, 200 ppm and 400 ppm. Percent viability of the eggs were measured at 1 hour post-incubation, while percentage hatch were measured at 24 hour post-incubation. Varying levels of water hardness did not show any significant effect in percentage viability.. Percentage hatching however showed to be high in hardness level of 100 ppm (27 {ogon} 4) and <100 ppm (26 {ogon} 3.43) but were significantly lowered in hardness levels of 400 ppm (11 {ogon} 2.56) and 200 ppm (5 {ogon} 1.32). The study suggests that a water hardness range of 100 or lesser is best for the incubation of catfish eggs in hatcheries.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Catfish, Asian